Answer:
(-7/9)^4 = 2401/6561
Step-by-step explanation:
The rules of exponents apply.
(a^b)/(a^c) = a^(b-c) . . . . . quotient rule
(a^b)^c = a^(bc) . . . . . . . . power rule
__
The first rule of exponents shown above helps us find the value of a/b.
[tex]\dfrac{a}{b}=\dfrac{\left(\dfrac{-7}{9}\right)^8}{\left(\dfrac{-7}{9}\right)^6}=\left(\dfrac{-7}{9}\right)^{8-6}=\left(\dfrac{-7}{9}\right)^2[/tex]
The second rule of exponents shown above tells us how to find the square.
[tex]\left(\dfrac{a}{b}\right)^2=\left(\left(\dfrac{-7}{9}\right)^2\right)^2=\left(\dfrac{-7}{9}\right)^{2\times2}\\\\\boxed{\left(\dfrac{a}{b}\right)^2=\left(\dfrac{-7}{9}\right)^4=\dfrac{2401}{6561}}[/tex]
_____
Additional comment
Since -7 is always to an even power in these expressions, its sign can be ignored. The product of an even number of negative values is positive.